Предмет: Математика,
автор: FlakeGod
Решите уравнение 6х(х+1)-(х+1)(х-2)=68
Ответы
Автор ответа:
0
6x^2+6x-x^2+2x-x+2=68
5x^2+7x=66
5x^2+7x-66=0
D=49-4*5*(-66)=1369
x1=-7+3710=3
x2=-7-3710=-4,4
Ответ: 3, -4,4
5x^2+7x=66
5x^2+7x-66=0
D=49-4*5*(-66)=1369
x1=-7+3710=3
x2=-7-3710=-4,4
Ответ: 3, -4,4
Похожие вопросы
Предмет: Математика,
автор: rozili2008
Предмет: Математика,
автор: nazkaashirbekova
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: mnalibaeva
Предмет: Литература,
автор: Kartushina